Intrinsic Learning Motivation and Academic Achievement of Senior High School Students - Dinda Aulia Febriyanti; Evelyn Agusta Putri; Dewangga Alfa Bimantara (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to examine the relationship between intrinsic learning motivation and academic achievement among high school students. The importance of this study lies in understanding how internal factors such as interest, curiosity, and self-determination can influence students' academic outcomes. Using a quantitative method, the study surveyed 120 students from various high schools in Semarang. The data were analyzed using Pearson correlation and regression analysis. The results indicated a significant positive relationship between intrinsic motivation and academic performance. These findings suggest the importance of nurturing intrinsic motivation as a pathway to improving academic outcomes.